2008
DOI: 10.1136/bjo.2007.130286
|View full text |Cite
|
Sign up to set email alerts
|

Autofluorescence of choroidal melanoma in 51 cases

Abstract: Choroidal melanoma generally shows slight intrinsic hyperautofluorescence and the brightness increases with pigmented tumours, larger tumours, and those associated with disrupted RPE. Overlying orange pigment shows remarkably bright hyperautofluorescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 23 publications
2
32
0
2
Order By: Relevance
“…Lavinsky et al 7 studied 20 melanocytic lesions and concluded that choroidal nevi did not show hyper-AF features, but choroidal melanomas showed a pattern of confluent hyper-AF. Shields et al 2,3 studied the AF of choroidal nevus in 64 cases and choroidal melanoma in 51 cases. They indicated that intrinsic AF was minimal in both nevus and melanoma, but extrinsic AF was strikingly different.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lavinsky et al 7 studied 20 melanocytic lesions and concluded that choroidal nevi did not show hyper-AF features, but choroidal melanomas showed a pattern of confluent hyper-AF. Shields et al 2,3 studied the AF of choroidal nevus in 64 cases and choroidal melanoma in 51 cases. They indicated that intrinsic AF was minimal in both nevus and melanoma, but extrinsic AF was strikingly different.…”
Section: Discussionmentioning
confidence: 99%
“…1 There are only a few reports on AF of choroidal tumors, including choroidal nevus and melanoma. [2][3][4][5][6][7] Choroidal nevus tends to impart RPE atrophy with hypo-AF of the RPE, whereas choroidal melanoma tends to show overlying orange pigment with hyper-AF of the RPE. Intrinsic AF of both tumors is minimal.…”
mentioning
confidence: 99%
“…As per the authors experience, this hyperAF is more intense than that of any other intraocular lesion. 3,4 There were 4 eyes with spontaneously regressed retinoblastoma, and all showed markedly hyperAF in the region of calcification and isoAF in the region of noncalcification. In the single eye with no previous treatment, AF was useful to delineate the scattered areas of calcification, which appeared brightly hyperAF.…”
Section: Discussionmentioning
confidence: 98%
“…The autofluorescent features of choroidal tumors such as melanoma, nevus, and metastasis have been described in the literature. [3][4][5][6][7] In this analysis, we evaluate the AF of treated retinoblastomas and correlate these findings with clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…Modern fundus cameras exploit this property to obtain autofluorescence fundus photographs highlighting areas of presumed increased accumulation of RPE lipofuscin ( Autofluorescence photography is often very useful when diagnosing intraocular tumors, especially of the choroid. Increased autofluorescence of overlying RPE is characteristic of choroidal melanoma [18,19], choroidal nevi that are more likely to transform into uveal melanoma [20], choroidal hemangioma [8], retinal lymphoma [21] and retinal pigment epithelial tissue which has been damaged as a result of fluid exuded from a tumor. One very useful way to differentiate choroidal melanoma from choroidal nevus is by the presence of orange pigment (lipofuscin) clumping overlying the former, which is hyperautofluorescent (FIGURES 9 & 10D).…”
Section: Autofluorescencementioning
confidence: 98%